Forts in the United Arab Emirates: Historical Backgrounds and Cultural Roles Between Past and Present: القلاع في الإمارات العربية المتحدة خلفياتها التاريخية وأدوارها الحضارية بين الماضى والحاضر - Amnah Ahmed Sobir al-Tanhani; Abdul Hamid , Faisal @ Ahmad Faisal (Journal Al-Muqaddimah, 2025)
This study addresses the forts in the United Arab Emirates as an extremely important and significant part of the architectural, defensive, and political heritage of the UAE, as these forts represent important historical symbols that reflect a portion of the historical role and strategic importance of the Emirates throughout the ages. The research reviews the historical, geographical, and political backgrounds that contributed to the construction of these forts and their vital role in protecting the people of these lands from external attacks. Therefore, it not only tracks the reasons for their establishment but also focuses on their architectural design and their defensive and political functions. The study also explores how the forts evolved from purely defensive structures to administrative, cultural, and tourist centers over time, pointing to the architectural and technological transformations that influenced their design and the impact they had on their roles at each stage. Furthermore, the research discusses the current efforts to preserve and maintain these forts, including restoration processes and the challenges they face, such as the effects of environmental factors and climate change. Thus, the study represents a valuable contribution to the field of cultural and architectural heritage studies in the United Arab Emirates In support of its distinctive identity, which is considered one of the most important features of its civilizational stability.